2017
DOI: 10.15672/hjms.2017.417
|View full text |Cite
|
Sign up to set email alerts
|

Modified tests for comparison of group means under heteroskedasticity and non-normality caused by outlier(s)

Abstract: There are several approximate tests proposed such as Welch's F-test (W), the Parametric Bootstrap Test (PB) and Generalized F-test (GF) for comparing several group means under heteroskedasticity. These tests are powerful and have nominal type 1 error rates but they are not performing satisfactorily under non-normality caused by outlier(s). To handle this problem, we investigate tests that are powerful and provide nominal type 1 error rates by using robust estimators both for location and scale parameters. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The study also discussed two possible modifications of a procedure commonly employed in the studies to better satisfy the conditions of the CLT (see https://osf.io/kn8mh/ for computer simulations of these modified procedures). Some commonly used parametric statistical tests, such as the t-test and the ANOVA (see also Tan and Tabatabai, 1985;Fan and Hancock, 2012;Cavus et al, 2017 for the robust-ANOVA) are robust to some extent against some types of nonnormality of the population (see Lumley et al, 2002 for a review) but not against some other types of non-normality, e.g., heavy tails and outliers (Cressie and Whitford, 1986;Wilcox, 2012). Note that there are some non-parametric statistical tests that do not use a normality assumption for the population but these non-parametric tests are not universally more robust than the parametric tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also discussed two possible modifications of a procedure commonly employed in the studies to better satisfy the conditions of the CLT (see https://osf.io/kn8mh/ for computer simulations of these modified procedures). Some commonly used parametric statistical tests, such as the t-test and the ANOVA (see also Tan and Tabatabai, 1985;Fan and Hancock, 2012;Cavus et al, 2017 for the robust-ANOVA) are robust to some extent against some types of nonnormality of the population (see Lumley et al, 2002 for a review) but not against some other types of non-normality, e.g., heavy tails and outliers (Cressie and Whitford, 1986;Wilcox, 2012). Note that there are some non-parametric statistical tests that do not use a normality assumption for the population but these non-parametric tests are not universally more robust than the parametric tests.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental Psychologists should check their row data and should discuss “effects” only if the effects are clear in their data. If they want to make inferences based on the results of statistical analyses, more modern statistical methods should be considered: e.g., Robust statistics (Tan and Tabatabai, 1985 ; Huber and Ronchetti, 2009 ; Fan and Hancock, 2012 ; Wilcox, 2012 ; Cavus et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yazici and Cavus (2021) discussed the performance the GF test under various conditions. Cavus et al (2017) proposed the modified GF (MGF) test by replacing the maximum likelihood estimators of the sample mean and variance with Huber (1964)'s M-estimators to overcome non-normality caused by outlier(s). They conducted a Monte-Carlo simulation study to show the performance of the MGF in terms of power and Type I error probability.…”
Section: Generalized Behrens-fisher Problem In Case Of Non-normalitymentioning
confidence: 99%
“…It is clearly concluded that MGF has a serious problem controlling the Type I error probability when RGF outperforms others for most of the scenarios. Cavus et al (2017) showed that the MGF is the superior test for heteroscedasticity and non-normality caused by outliers. However, it could not maintain the performance for non-normality caused by skewness in terms of Type I error probability.…”
Section: Monte-carlo Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation